(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Banking in India originated in the last decades of the 18th century. The IT revolution influenced the Indian banking system a lot. The use of computers had led to existence of online banking in India. The use of modern innovation and computerisation of the banking sector of India has increased many folds after the economic liberalisation of 1991 as the country’s banking sector has been exposed to the world’s market. The Indian banks were finding it hard to compete with the international banks in terms of the customer service without the use of the information technology and computers. Internet banking as a medium of delivery of banking services and as a strategic tool for business development, has gained wide acceptance internationally and is fast catching up in India with more and more banks entering the fray. In the light of this background, the objective of this paper is to study the perceived usefulness of Internet Banking. This paper tries to know the level of awareness among customers. This paper also tries to check the perception of risks closely connected with Internet Banking and study the scope of Internet Banking, so that companies can fulfill their duty in an appropriate and suitable manner.